Propuesta de mejora para el proceso de fabricación de empaques de caucho natural en industrias Jolferb (2017)
This work proposes an improvement proposal for the rubber packaging manufactured in Jolferb industries, making a characterization of the natural rubber packaging produced by the company, using it as a basis to elaborate a new formulation together with a protocol that Help to reduce the nonconformities presented by the clients of industries JOLFERB. The development of the characterization was done both to the formula based on natural rubber and to the formula of the proposed alternative, starting from factors that influence the quality of the films that are manufactured in the company. In order to later analyze the influence of two factors that influence the hardness of the material, which is the main nonconformity of the customer, an experimental design was made with the factors of vulcanization times and amount of plasticizer, having for the same two levels of 8 and 12 Minutes and 1500 and 2000 grams respectively. From this it was identified that the concentration of plasticizer most suitable for the new formulation is 2000 gr using a vulcanization time of 8 minutes, since under these conditions the final product has the required hardnesses. A sheet was fabricated using the data of the experimental part, comparing it with the sheets manufactured in the company, it was found that the flexural, tensile and hardness properties are improved, obtaining in this way a product of better quality. Finally, we compared the profitability for the traditional process and for the proposed alternative, in order to see the viability of the proposal and the improvement of this profitability with the new formulation.